2005
DOI: 10.1007/11496137_11
|View full text |Cite
|
Sign up to set email alerts
|

Thompson’s Group and Public Key Cryptography

Abstract: Abstract. Recently, several public key exchange protocols based on symbolic computation in non-commutative (semi)groups were proposed as a more efficient alternative to well established protocols based on numeric computation. Notably, the protocols due to Anshel-Anshel-Goldfeld and Ko-Lee et al. exploited the conjugacy search problem in groups, which is a ramification of the discrete logarithm problem. However, it is a prevalent opinion now that the conjugacy search problem alone is unlikely to provide suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 7 publications
(13 reference statements)
0
89
0
10
Order By: Relevance
“…Схема формирования ключа в протоколе Хехта является частным случаем схемы из протокола Шпильрайна Ушакова [2].…”
Section: д д болотов е а магдинunclassified
“…Схема формирования ключа в протоколе Хехта является частным случаем схемы из протокола Шпильрайна Ушакова [2].…”
Section: д д болотов е а магдинunclassified
“…A whole branch of new protocols was developed which do not rely on extended arithmetic's precision and instead exploit internal asymmetry of abstract algebraic structures like partial grupoids, categories, magmas, monoids, quasigroups, groups, rings, loops or neofields [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The new developed one-way trapdoor functions (OWTF) include conjugator search (CSP), decomposition (DP), commutative subgroup search (CSSP), symmetric decomposition (SDP) and generalized symmetric decomposition (GSDP) [9,15,17,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The protocol below was suggested by Shpilrain and Ushakov in [12]. The authors suggested to use Thompson's group F for its implementation.…”
Section: The Shpilrain-ushakov Key Agreement Protocolmentioning
confidence: 99%
“…The best known example of such a protocol is the Diffie-Hellman protocol, which uses a (commutative) cyclic group. Over the last few years, there was a lot of interest in key agreement protocols based on noncommutative groups, and much research was dedicated to analyzing these proposals and suggesting alternative ones (see, e.g., [1,4,5,6,7,8,10,11,12], and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation